Microwave synthesis of high-quality and uniform 4 nm ZnFe2O4 nanocrystals for application in energy storage and nanomagnetics - Suchomski, Christian; Breitung, Ben; Witte, Ralf; Knapp, Michael; Bauer, Sondes; Baumbach, Tilo; Reitz, Christian; Brezesinski, Torsten (Beilstein Journal of Nanotechnology, 2016)
Magnetic nanocrystals with a narrow size distribution hold promise for many applications in different areas ranging from biomedicine to electronics and energy storage. Herein, the microwave-assisted sol–gel synthesis and thorough characterization of size-monodisperse zinc ferrite nanoparticles of spherical shape is reported. X-ray diffraction, 57Fe Mössbauer spectroscopy and X-ray photoelectron spectroscopy all show that the material is both chemically and phase-pure and adopts a partially inverted spinel structure with Fe3+ ions residing on tetrahedral and octahedral sites according to (Zn0.32Fe0.68)tet[Zn0.68Fe1.32]octO4±δ. Electron microscopy and direct-current magnetometry confirm the size uniformity of the nanocrystals, while frequency-dependent alternating-current magnetic susceptibility measurements indicate the presence of a superspin glass state with a freezing temperature of about 22 K. Furthermore, as demonstrated by galvanostatic charge–discharge tests and ex situ X-ray absorption near edge structure spectroscopy, the as-prepared zinc ferrite nanocrystals can be used as a high-capacity anode material for Li-ion batteries, showing little capacity fade – after activation – over hundreds of cycles. Overall, in addition to the good material characteristics, it is remarkable that the microwave-based synthetic route is simple, easily reproducible and scalable.
Keywords: 1-phenylethanol route; lithium-ion battery; nanomagnetism; nanoparticles; nonaqueous sol–gel synthesis; zinc ferrite